Acute appendicitis and acute mesenteric adenitis in children: Are they clinically distinguishable? - Pokhrel, Manish (Journal of Kathmandu Medical College, 2020)
Background: Acute appendicitis and acute mesenteric adenitis have very similar clinical presentations but radically different treatment approaches in children.Objectives: This study aims to test the possibility of clinically distinguishing between acute appendicitis and acute mesenteric adenitis.Methodology: A cross-sectional study was designed to recruit all children (